2018
DOI: 10.1007/s00464-017-5974-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome trends and safety measures after 30 years of laparoscopic cholecystectomy: a systematic review and pooled data analysis

Abstract: BackgroundLaparoscopic cholecystectomy (LC), one of the most commonly performed surgical procedures, remains associated with significant major morbidity including bile leak and bile duct injury (BDI). The effect of changes in practice over time, and of interventions to improve patient safety, on morbidity rates is not well understood. The aim of this review was to describe current incidence rates and trends for BDI and other complications during and after LC, and to identify risk factors and preventative measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
143
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(160 citation statements)
references
References 32 publications
3
143
3
11
Order By: Relevance
“…13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis. 13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis. 13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy remains the most common minimally invasive biliary surgery performed worldwide today and it is now regarded as the gold standard approach of choice. 13,14 However, its use is mainly limited to relatively straightforward conditions such as biliary colic, symptomatic gallstones and early acute cholecystitis. 13,14 When applied to more complicated conditions such as perforated/gangrenous cholecystitis, 15 choledocholithiasis 16 and Mirizzi syndrome, 17,18 the laparoscopic approach has been reported to be associated with high open conversion rates of up to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 151 studies showed that rates of bile duct injury (BDI) have been reduced over time (1994-1999: 0.69% (0.52-0.84%) versus 2010-2015: 0.22% (0.02-0.40%), P = 0.011). 3 However, a recent database review study of BDI showed that less experienced surgeons reported BDI rates three times higher than their more experienced counterparts. 4 Additionally, a European-based population study showed that high volume centres (defined as >244 LC/year) reported lower morbidity, mortality and reoperation rates, 5 suggesting a relationship between case volume and BDI frequency.…”
mentioning
confidence: 99%
“…A systematic review of 151 studies showed that rates of bile duct injury (BDI) have been reduced over time (1994–1999: 0.69% (0.52–0.84%) versus 2010–2015: 0.22% (0.02–0.40%), P = 0.011) . However, a recent database review study of BDI showed that less experienced surgeons reported BDI rates three times higher than their more experienced counterparts .…”
mentioning
confidence: 99%
See 1 more Smart Citation